PEMODELAN DINAMIK KUALITAS AIR PADA BUDIDAYA IKAN NILA (Oreochromis niloticus ) DI PERAIRAN RAWA - Fatmawati Fatmawati; Noor Arida Fauzana (Universitas Lambung Mangkurat, 2014)
Increased feeding at the waste of feed and feces are discharged into the aquatic environment make increase the consumption of dissolved oxygen to decompose. If it continues, there will be an aerobic and reductive conditions, especially in bottom water, they will be accelerate the decomposition of organic material in aerobic to produce toxic materials which endanger the fish. Purpose of this study was simulate the dynamic model of water quality in tilapia farming in the swamp waters, so can make a good scenario in produced tilapia farming activities in production of appropriate sustainable land productivity capabilities. Data analysis of dynamic model was performed with Power Sim Studio 5. simulation results showed the growth of tilapia with probiotics feed better than without probiotic feed, and environmental improvements swamp waters. Recommended on first scenario (one crop) and second scenario (two crops) in a year , there is a time break of reproduction if harvest done 1-2 times a year for recovery (self purification) natural wetlands, then can create more sustainable aquaculture. The third simulation (three harvests a year) are not recommended, because the land used continuously without a break will cause impaired water quality and impact on the decline in fish production as well as unsustainable.